The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/aps.2016.45
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the analgesic effects of ammoxetine, a novel potent serotonin and norepinephrine reuptake inhibitor

Abstract: Aim:The selective serotonin (5-HT) and norepinephrine (NE) reuptake inhibitors (SNRIs) are commonly used for the treatment of neuropathic pain and fibromyalgia. Ammoxetine ((±)-3-(benzo [d] [1,3]dioxol-4-yloxy)-N-methyl-3-(thiophen-2-yl)propan-1-amine) has been identified as a novel potent SNRI. In this study, we evaluated the acute analgesic properties of ammoxetine in different animal models of pain, and examined the involvement of monoamines in its analgesic actions. Methods: The analgesic effects of ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…46,47 Reserpine treatment causes reduced mechanical and thermal nociceptive thresholds in rodents, 48,49 indicative of good face validity for pain in PD. The antinociceptive effects of duloxetine in this model, 50 further support an involvement of reduced serotonergic and noradrenergic signalling in the mechanical and thermal hypersensitivity. However, these pharmacological effects are not totally in line with clinical outcomes, casting some doubt on the predictive validity of this model.…”
Section: Acute Pharmacological Modelssupporting
confidence: 74%
“…46,47 Reserpine treatment causes reduced mechanical and thermal nociceptive thresholds in rodents, 48,49 indicative of good face validity for pain in PD. The antinociceptive effects of duloxetine in this model, 50 further support an involvement of reduced serotonergic and noradrenergic signalling in the mechanical and thermal hypersensitivity. However, these pharmacological effects are not totally in line with clinical outcomes, casting some doubt on the predictive validity of this model.…”
Section: Acute Pharmacological Modelssupporting
confidence: 74%
“…Our published data have proved that ammoxetine is a potent and balanced SNRI with superior antidepressant activity and lower cytotoxicity in HepG2 cells compared to duloxetine [ 24 26 ]. Ammoxetine displays acute efficacy in reversing mechanical allodynia in models of neuropathic pain, fibromyalgia-related pain, and inflammatory pain [ 27 ]. In this study, we evaluated the efficacy of a chronic ammoxetine treatment in DNP in STZ-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…Noradrenaline is known to exert strong anti-inflammatory activity in the CNS (Mcnamee et al, 2010) and its endogenous neuroprotective role in chronic pain is likely linked to this action (Zhang et al, 2016b).…”
Section: Neuroinflammation and Microglial Activation In The Pathophysmentioning
confidence: 99%
“…β-Adrenergic receptors are also abundantly expressed in glial cells of the rat spinal dorsal horn (Mizukami, 2004; Nicholson et al, 2005), where their activation was shown to control nociceptive transduction by attenuating microglial reactivity (Morioka et al, 2009; Zhang et al, 2016b). Systematic treatment with β-adrenergic receptor agonists resulted in antinociceptive effects in animal models of neuropathic pain (Choucair-Jaafar et al, 2009).…”
Section: Neuroinflammation and Microglial Activation In The Pathophysmentioning
confidence: 99%
See 1 more Smart Citation